Dostoyevsky's Grand Inquisitor as a Mirror for the Ethics of Institutions - Bouckaert, Luk (Journal of business ethics, 2004)
The aim of the paper is twofold. On a methodological level we explore the way classic literary texts can be used as a resource for analysis and reflection in the field of business ethics. On the level of substance we use the story of the Grand Inquisitor to analyze the problem of hypocrisy in business ethics and leadership. To overcome the problem of hypocrisy we look for some clues in the work of Dostoyevsky himself.